Pengaruh Pendidikan Kesehatan Tentang Pijat Bayi terhadap Praktik Pijat Bayi - Ajeng Mahardika Wati; Nevy Norma Renityas (Journal of Ners and Midwifery, 2014)
Massage baby was done to smooth the surface of the skin performed by the hand which aims to produce effects of neurons, the muscles, respiratory systems and circulating blood and limpha.The aim of this research is to find out about babies health is the educational practices massage ain on an infant by the baby. Method: Research design was pretest-postest without control group designs. Research sample was 20 mother who have babies age 0-12 months in the BPS kirana, Jatinom Village, it choosed with purposive sampling. Analysis using wilcoxon, with significant level â‰¤0.05 Result: The results showed that health education of baby massage influence baby massage skill, with wilcoxon signed rank test obtained p-value 0,000. Discuss: With education about the expected health massage parents babies have knowledge and skills of massage infants it can massaging her baby independently and right.